From Vision To Reality: Overcoming The Challenges of Implementing E-Government in Papua - Nomensen Yeheskel Singgir; Dian Ferriswara; Ika Devy Pramudiana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to identify and analyze the main challenges in the implementation of e-government in Papua Province, employing a descriptive qualitative approach based on secondary data. Papua, with its unique geographical conditions and socio-cultural characteristics, faces considerable obstacles in digital transformation, despite national policies to accelerate the Electronic-Based Government System (SPBE). The analysis highlights several key challenges, including limited ICT infrastructure, low digital literacy, weak system interoperability, cultural resistance, and the absence of adaptive regulatory frameworks. To comprehensively interpret these complexities, this research integrates multiple theoretical lenses, namely the Technology-Organization-Environment (TOE) framework, the Unified Theory of Acceptance and Use of Technology (UTAUT), ICT readiness, and organizational resistance theory. Findings reveal that while Papua’s internet penetration rate has reached 69.91%, the adoption and utilization of public digital services remain significantly low. This gap reflects a disconnect between technological availability and institutional as well as cultural readiness. Moreover, the lack of involvement of local communities and indigenous leaders in the design and implementation of digital services has exacerbated the challenges of public acceptance and trust in government-led innovations. These limitations not only hinder service delivery but also create disparities in the broader agenda of equitable digital transformation across Indonesia. In response, this study recommends several strategic solutions: strengthening ICT infrastructure to reduce connectivity disparities, enhancing digital literacy programs tailored to local needs, drafting regulations that are context-sensitive and flexible, and applying cultural-based as well as participatory approaches to increase legitimacy and acceptance. By doing so, e-government initiatives in Papua can become more inclusive, sustainable, and effective. Overall, this study contributes to the literature on e-government in disadvantaged and high-complexity regions, emphasizing the urgency of inclusive and equitable digital policy design.